2012
DOI: 10.1124/mol.112.080523
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine Endocannabinoid Signaling through CB1Receptors Potentiates OX1Orexin Receptor Signaling

Abstract: It has been proposed that OX 1 orexin receptors and CB 1 cannabinoid receptors can form heteromeric complexes, which affect the trafficking of OX 1 receptors and potentiate OX 1 receptor signaling to extracellular signal-regulated kinase (ERK). We have recently shown that OX 1 receptor activity releases high levels of the endocannabinoid 2-arachidonoyl glycerol (2-AG), suggesting an alternative route for OX 1 -CB 1 receptor interaction in signaling, for instance, in retrograde synaptic transmission. In the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 57 publications
3
33
0
Order By: Relevance
“…Besides the heteromerization, an additional mechanism has been proposed to explain the increase in the potency of hypocretin-1 to activate the ERK pathway in the presence of CB1 (Jäntti et al, 2013; Kukkonen and Leonard, 2013). Recent studies report that HcrtR1-expressing CHO cells may release 2-AG in response to hypocretin-1 stimulation.…”
Section: Molecular Interactions Between Cb1 and Hcrtr1mentioning
confidence: 99%
“…Besides the heteromerization, an additional mechanism has been proposed to explain the increase in the potency of hypocretin-1 to activate the ERK pathway in the presence of CB1 (Jäntti et al, 2013; Kukkonen and Leonard, 2013). Recent studies report that HcrtR1-expressing CHO cells may release 2-AG in response to hypocretin-1 stimulation.…”
Section: Molecular Interactions Between Cb1 and Hcrtr1mentioning
confidence: 99%
“…In any biological system, the abundance of endogenously-produced endocannabinoids is an important determinant of whether the CB 1 R is under the influence of high “endocannabinoid tone” that could be reversed by a competitive antagonist (for discussion, see [42]). CHO cells express phospholipase C and diacylglycerol lipase [43;44], as do neuronal cell lines (Howlett, unpublished observations), enzymes that govern production of the endocannabinoid 2-AG. This suggests the necessity of testing responses to a diaceylglycerol lipase inhibitor to demonstrate whether forskolin-activated cAMP accumulation can be influenced by endocannabinoids produced by the cultured cells.…”
Section: Discussionmentioning
confidence: 99%
“…25 In an in vitro study, it was demonstrated that the coexpression of CB1 and OX1 receptors results in a higher potentiation of ERK signalling, possibly because of heterodimerization/oligomerization of these two receptors. 26 Recently, however, it was also shown that 2-AG produced and released through the activation of OX1 receptor acts as both a paracrine and autocrine messenger via CB1 receptors, 23,27 thus possibly explaining the above-mentioned findings in the rat dorsal raphe nucleus and periaqueductal gray, as well as the potentiation of ERK phoshorylation that follows OX1/CB1 receptor coexpression. These data suggest the involvement of 2-AG and CB1 receptors not only in orexin-A release but also in orexin-mediated regulation of synaptic transmission.…”
Section: Leptin-mediated Hypothalamic Ecb/orexin Interactionsmentioning
confidence: 94%